The Association of Obesity and School Absenteeism Attributed to Illness or Injury Among Adolescents in the United States, 2009 - Pan, Liping (J Adolesc Health, 2012)
PURPOSE: School attendance can impact academic performance. Childhood obesity-related physical and psychosocial consequences are potentially associated with school absenteeism. Thus, we examined the association between school absenteeism attributed to illness or injury and obesity among adolescents aged 12–17 years. METHODS: We used a weighted sample of 3,470 U.S. adolescents from the 2009 National Health Interview Survey. School absenteeism was measured from the parent-reported number of sick days taken in the preceding 12 months. Body mass index was calculated from parent-reported weight and height. Weight status was classified based on the sex-specific body mass index-for-age percentile defined by the CDC growth charts. Poisson regression was conducted to examine the association between school absenteeism and weight status, controlling for selected sociodemographic characteristics and disease status. RESULTS: The mean number of annual sick days was 3.9 days overall; 3.4 days among normal-weight, 4.4 days among overweight, and 4.5 days among obese adolescents. Obese adolescents had a higher proportion of missing ≥4 days of school per year than adolescents of normal weight. Our multivariate analyses found that compared with adolescents of normal weight, overweight and obese adolescents had greater than one-third more sick days annually (rate ratio = 1.36 for overweight and 1.37 for obese adolescents). CONCLUSIONS: Overweight and obese adolescents had 36% and 37% more sick days, respectively, than adolescents of normal weight. The results suggest another potential aspect of obesity prevention and reduction efforts among children and families is to improve children’s school attendance.